Religion and the university - Pelikan, Jaroslav, 1923-2006 (Univ. of Toronto Press, 1964)
During the 1964 winter term, distinguished scholars presented the Frank Gerstein Lecture at York University. The theme ""Religion and the University"" was selected because of a desire to raise some important and highly relevant questions concerning the place and nature of religion in the university.